Empirical Fragility Curves for Non-Residential Buildings from the 2010–2011 Canterbury Earthquake Sequence. Issue 5 (28th May 2018) - Lin, Sheng-Lin; Uma, S. R.; King, Andrew
ABSTRACT: This study develops a motion-damage database (the Canterbury Earthquake Building Assessment, CEBA database) using surveyed information obtained from the Canterbury earthquake sequence. The database is then applied to derive fragility curves for non-residential buildings in New Zealand. The results indicate that unreinforced masonry buildings are the most vulnerable to damage, while the concrete shear wall buildings were found to be the most resilient. Discrepancies were found when comparing equivalent structures in New Zealand and the United States. Inherent difference of building characteristics between the two countries, significant ground failure, and accumulated damage from multiple events might explain the difference.